Long-term exposure to irinotecan reduces cell migration in glioma cells. - Al-Ghafari, Ayat B.; Punjaruk, Wiyada; Storer, L.C.D.; Carrier, D.J.; Hussein, D.; Coyle, Beth; Kerr, Ian D. (Springer, 2016)
In spite of considerable research into the therapies for glioblastoma multiforme this tumour type remains very difficult to treat. As well as having a tendency to be inherently resistant to chemotherapy, glioblastoma multiforme also displays local invasion. Cell line studies have a continued and important role to play in understanding the mechanisms associated with both chemotherapy resistance and invasion. In the current study we have utilized the C6 glioma cell line to investigate the response to long-term, clinically relevant application of topoisomerase I and II inhibitors. Treatment with etoposide resulted in an increase in resistance to this topoisomerase II inhibitor. By contrast, the continuous exposure to a topoisomerase I inhibitor did not result in increased drug resistance, but was associated with a reduction in cell migration. This data supports further investigation of topoisomerase I inhibition as a means to inhibit glioma invasion without the development of parallel chemoresistance.